THE ROLE OF THIRD PARTIES IN IMPLEMENTING PERSONALITY DEVELOPMENT IN THE FIELD OF RELIGIOUS AWARENESS FOR PRISONERS IN BREBES CLASS IIB PRISON - Meisyahrul, Alif; Indahdewi, Lauditta (Universitas Nusa Cendana, 2025)
The aim of this study is to find out the role of third parties in implementing personality development in the field of religious awareness for prisoners and to find out what obstacles are experienced by third parties in implementing personality development in the field of religious awareness for prisoners. This research is field research using a qualitative descriptive approach. The theories used in this research are role theory and the SPPN concept (aspects of religious awareness). Data collection techniques were carried out by means of observation, interviews, literature study, and documentation. The results of data analysis using qualitative descriptive analysis, namely that the third party plays a role in implementing religious awareness development for prisoners by being responsible for being a coaching actor, providing material supplies, participating in implementing existing regulations, serving the community, and harmonizing religious teachings inside the prison with those outside the prison. Meanwhile, the obstacles faced by third parties are 1. The existence of a concurrent schedule from the third party carrying out the coaching; 2. there are activities in prison that overlap or are carried out at the same time; 3. lack of human resources from prison officers in carrying out training; 4. requires time for coordination between agencies; and 5. The prisoner's personality is poor in accepting material. Keywords: Role; Third Party; Religious Awareness